1996
DOI: 10.1063/1.363499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high oxygen partial pressure heat treatment on the superconducting properties of Bi2Sr2CaCu2Ox/Ag tapes

Abstract: We investigated the effect of oxygen partial pressure pO 2 during melt-and-solidification heat treatment on the superconducting properties of grain oriented Bi-2212 thick films. T c and c-axis parameter decreased with increasing pO 2 , indicating the samples were in the over-doped state. The heat treatment temperature which gave highest J c increased with increasing pO 2 . This was explained by the increase of the solidification temperature of Bi-2212 with pO 2 . Both the resistive J c and intergrain J c estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…• C. Manipulation of the overall Bi2212 composition and changing the cooling rate are some ways to raise J c [7][8][9][10], but really much is still unknown about what controls J c in wires. Recently we compared the separate contributions of superconducting connectivity and flux pinning to J c by varying the cooling rate [11] through the Bi2212 phase nucleation in a through-process quench study.…”
Section: Introductionmentioning
confidence: 99%
“…• C. Manipulation of the overall Bi2212 composition and changing the cooling rate are some ways to raise J c [7][8][9][10], but really much is still unknown about what controls J c in wires. Recently we compared the separate contributions of superconducting connectivity and flux pinning to J c by varying the cooling rate [11] through the Bi2212 phase nucleation in a through-process quench study.…”
Section: Introductionmentioning
confidence: 99%
“…and 885 "C for P02=0.01,0.21 and 1 atm, respectively [3]. The tapes were held at TmaX for 5 minutes, then cooled down at 10 K/hr for 5 hrs, and finally furnace-cooled to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the J, was influenced by oxygen partial pressure (Poz) during processing [3]-[SI. We reported that the J, values of Bi-2212/Ag tapes were 0.5, 1.2 and 2x105 Ncm2 (4.2 K,10 T) when processed in P02=0.01, 0.21 and 1 atm, respectively [3].…”
Section: Introductionmentioning
confidence: 99%
“…Much discussion on improving conductor J c deals with manipulating the melt phase assemblages. 11 Here, we concentrate on the final portion of the heat treatment, which occurs after forming the Bi-2212 network, where we enhance the superconducting connectivity by slow cooling in an O 2 -rich atmosphere.…”
mentioning
confidence: 99%